Lithium-ion battery
By employing intermetallic compounds like La3Ni2Sn7 and ammonium carboxymethyl cellulose (NH4-CMC) in the negative electrode mixture layer, the challenges of high costs, volume changes, and reaction inhibition in lithium ion batteries are addressed, resulting in improved capacity retention and cycle stability.
Patent Information
- Application Number
- JP2022512280
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-02
- Filing Date
- 2021-03-30
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-03-30
AI Technical Summary
Graphite-based negative electrode active materials in lithium ion batteries face issues such as high costs, volume changes during charging and discharging, and decreased capacity retention, while traditional binders like PVdF cause gelation and alloying reactions, inhibiting effective coating and cycle characteristics.
The use of intermetallic compounds like La3Ni2Sn7 with a specific particle size and a water-based binder, such as ammonium carboxymethyl cellulose (NH4-CMC), to form the negative electrode mixture layer, which suppresses gelation and alloying reactions, enabling efficient coating and maintaining capacity and cycle characteristics.
This configuration results in improved capacity retention and cycle stability, allowing for cost-effective production of lithium ion batteries with enhanced performance.
Smart Images

Figure 0007599138000002 
Figure 0007599138000003 
Figure 0007599138000004
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a lithium-ion battery that includes a positive electrode having a positive electrode mixture layer containing a positive electrode active material, a negative electrode having a negative electrode mixture layer containing a negative electrode active material, and is charged and discharged by the movement of lithium ions between the positive electrode and the negative electrode. [Background technology]
[0002] Lithium-ion batteries, which are charged and discharged by the movement of lithium ions (Li ions) between the negative and positive electrodes, are widely used. Graphite-based materials are often used as the negative electrode active material in the negative electrode mixture layer of these lithium-ion batteries. Graphite-based negative electrode active materials are sometimes used together with silicon, which causes a large volume change during charging and discharging, which tends to deteriorate the capacity retention characteristics and is relatively expensive.
[0003] Therefore, anode active materials other than graphite have been proposed. For example, Patent Document 1 proposes La 3 Co 2 Sn 7 The use of alloys having a type crystal structure is described.
[0004] In addition, a binder is used in the negative electrode mixture layer to prevent peeling and cracking, but if the amount of binder increases, the efficiency of the battery reaction of the negative electrode active material decreases, so there is a demand to reduce the amount of binder. Patent Document 2 describes that the binder content is 0.5 mass% or more and 5.0 mass%. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 4127692 [Patent Document 2] JP 2007-258127 A Summary of the Invention
[0006] In Patent Document 1, polyvinylidene fluoride (PVdF) is used as a binder, but experimental results show that La 3 Co 2 Sn 7 It was found that when an alloy having a La type crystal structure is used and PVdF is used as a binder, the mixture slurry used to form the negative electrode mixture layer gels due to the reaction between the two, making coating difficult. 3 Ni 2 Sn 7 In order to reduce the reactivity of PVdF with the negative electrode active material and make it possible to apply the material, it is necessary to increase the particle size of the negative electrode active material. However, increasing the particle size of the negative electrode active material reduces the reactivity of the negative electrode active material with Li, which tends to reduce the capacity.
[0007] In addition, depending on the binder, La 3 Co 2 Sn 7 In some cases, alloys having the above-mentioned crystal structure undergo an alloying reaction to form impurity alloys, which reduces cycle characteristics.
[0008] The lithium ion battery according to the present disclosure includes a positive electrode having a positive electrode mixture layer containing a positive electrode active material, and a negative electrode having a negative electrode mixture layer containing a negative electrode active material, and is a lithium ion battery in which charging and discharging are performed by the movement of lithium ions between the positive electrode and the negative electrode, and the negative electrode mixture layer is represented by a general formula M 3 Me 2 X 7 (wherein M includes at least one selected from the group consisting of La, Ce, Ba, Sr, Zr, Ca, Mg, and Y, Me includes at least one selected from the group consisting of Ti, V, Cr, Nb, Mn, Ni, Fe, Co, and Cu, and X includes at least one selected from the group consisting of Ge, Si, Sn, Al, P, Sb, and B), and ammonium carboxymethyl cellulose (NH 4 -CMC) and a binder.
[0009] The lithium ion battery according to the present disclosure includes a positive electrode having a positive electrode mixture layer containing a positive electrode active material, and a negative electrode having a negative electrode mixture layer containing a negative electrode active material, and is a lithium ion battery in which charging and discharging are performed by the movement of lithium ions between the positive electrode and the negative electrode, and the negative electrode mixture layer is a compound represented by the general formula M 3 Me 2 X 7 (wherein M includes at least one selected from the group consisting of La, Sr, Ca, Mg, and Y, Me includes at least one selected from the group consisting of Mn, Ni, Fe, Co, and Cu, and X includes at least one selected from the group consisting of Ge, Si, Sn, Al, and B), and ammonium carboxymethyl cellulose (NH 4 -CMC) and a binder.
[0010] In this disclosure, La is used as the negative electrode active material. 3 Ni 2 Sn 7 Etc., general formula M 3 Me 2 X 7 (wherein M includes at least one selected from the group consisting of La, Ce, Ba, Sr, Zr, Ca, Mg, and Y, Me includes at least one selected from the group consisting of Ti, V, Cr, Nb, Mn, Ni, Fe, Co, and Cu, and X includes at least one selected from the group consisting of Ge, Si, Sn, Al, P, Sb, and B) is used to enable coating of the negative electrode mixture layer while suppressing a decrease in capacity and a decrease in cycle characteristics. In addition, the use of a water-based binder makes it possible to perform coating at low cost. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a longitudinal sectional view of a cylindrical secondary battery 10 according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram showing X-ray diffraction patterns of the electrodes according to the example and the comparative example. [Figure 3A] FIG. 3A is a graph showing charge / discharge characteristics in an example, and is a diagram showing the relationship between capacity and electrode potential. [Figure 3B] FIG. 3B is a graph showing charge / discharge characteristics in an example, and is a diagram showing the relationship between the number of cycles and the capacity. [Figure 4] FIG. 4 is a graph showing the charge-discharge characteristics of Comparative Example 1 in which SBR / Na-CMC was used as the negative electrode binder. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. Note that the present disclosure is not limited to the embodiments described herein.
[0013] [About negative electrode materials] The negative electrode material of a lithium-ion battery is preferably one that satisfies the requirements of high energy density and low expansion. Therefore, various research and development efforts are being carried out, and La 3 Ni 2 Sn 7 M 3 Me 2 X 7 It has been proposed to use intermetallic compounds represented by the formula (M = La, Ca, Me = Mn, Ni, Fe, Co, X = Ge, Si, Sn, Al). Such intermetallic compounds absorb and release Li through an intercalation reaction, so they have a low expansion rate and are thought to have a long life.
[0014] However, it was found that this material needs further improvement before it can be used in practice. First, as mentioned above, when PVdF is used as a binder, the negative electrode mixture slurry gels, making it difficult to coat the negative electrode mixture layer. In addition, suppressing gelation by increasing the particle size of the binder may inhibit the battery reaction.
[0015] In addition, gelation of the negative electrode mixture slurry can be suppressed by using a binder containing a cyano group, such as polyacrylonitrile (PAN). However, PAN is an organic binder, and requires coating using an organic solvent, which means that coating cannot be performed inexpensively.
[0016] Furthermore, when polyimide (PI) and styrene butadiene rubber / sodium salt carboxymethyl cellulose (SBR / Na-CMC) were used, the negative electrode active material La 3 Ni 2 Sn 7 This may cause an alloying reaction with the alloy of the type crystal, resulting in a decrease in cycle characteristics.
[0017] [Configuration of the embodiment] FIG. 1 is a longitudinal cross-sectional view of a cylindrical secondary battery 10 as an example of an embodiment. In the secondary battery 10 shown in FIG. 1, an electrode body 14 and a non-aqueous electrolyte are housed in an exterior body 15. The electrode body 14 has a wound structure in which a positive electrode 11 and a negative electrode 12 are wound with a separator 13 interposed therebetween. As a non-aqueous solvent (organic solvent) for the non-aqueous electrolyte, carbonates, lactones, ethers, ketones, esters, etc. can be used, and these solvents can be used in a mixture of two or more kinds. When using a mixture of two or more kinds of solvents, it is preferable to use a mixed solvent containing a cyclic carbonate and a chain carbonate. For example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc. can be used as the cyclic carbonate, and dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc. can be used as the chain carbonate. The electrolyte salt for the non-aqueous electrolyte is LiPF 6 , LiBF 4 , LiCF 3 SO 3 etc., and mixtures thereof can be used. The amount of electrolyte salt dissolved in the non-aqueous solvent can be, for example, 0.5 to 2.0 mol / L. For convenience of explanation, the following description will be given with the sealing body 16 side as the "upper" and the bottom side of the exterior body 15 as the "lower".
[0018] The opening end of the exterior body 15 is closed with the sealing body 16, so that the inside of the secondary battery 10 is sealed. Insulating plates 17 and 18 are provided above and below the electrode body 14, respectively. The positive electrode lead 19 extends upward through the through hole of the insulating plate 17 and is welded to the underside of the filter 22, which is the bottom plate of the sealing body 16. In the secondary battery 10, the cap 26, which is the top plate of the sealing body 16 electrically connected to the filter 22, serves as the positive electrode terminal. On the other hand, the negative electrode lead 20 extends through the through hole of the insulating plate 18 to the bottom side of the exterior body 15 and is welded to the inner bottom surface of the exterior body 15. In the secondary battery 10, the exterior body 15 serves as the negative electrode terminal. In addition, when the negative electrode lead 20 is installed at the terminal portion, the negative electrode lead 20 passes outside the insulating plate 18, extends to the bottom side of the exterior body 15, and is welded to the inner bottom surface of the exterior body 15.
[0019] The exterior body 15 is, for example, a cylindrical metal exterior can with a bottom. A gasket 27 is provided between the exterior body 15 and the sealing body 16 to ensure the sealing of the inside of the secondary battery 10. The exterior body 15 has a grooved portion 21 that supports the sealing body 16 and is formed, for example, by pressing a side portion from the outside. The grooved portion 21 is preferably formed in an annular shape along the circumferential direction of the exterior body 15, and supports the sealing body 16 on its upper surface via the gasket 27.
[0020] The sealing body 16 includes a filter 22, a lower valve body 23, an insulating member 24, an upper valve body 25, and a cap 26, which are stacked in this order from the electrode body 14 side. Each member constituting the sealing body 16 has, for example, a disk or ring shape, and each member except the insulating member 24 is electrically connected to each other. The lower valve body 23 and the upper valve body 25 are connected to each other at their respective centers, and the insulating member 24 is interposed between their respective peripheral edges. When the internal pressure of the battery increases due to abnormal heat generation, for example, the lower valve body 23 breaks, which causes the upper valve body 25 to swell toward the cap 26 and move away from the lower valve body 23, thereby cutting off the electrical connection between them. When the internal pressure further increases, the upper valve body 25 breaks, and gas is discharged from the opening 26a of the cap 26.
[0021] Hereinafter, the positive electrode 11, the negative electrode 12, and the separator 13 that constitute the electrode assembly 14 will be described, with particular reference to the negative electrode active material that constitutes the negative electrode 12.
[0022] [Positive electrode] The positive electrode 11 has a positive electrode core and a positive electrode mixture layer provided on the surface of the positive electrode core. For the positive electrode core, a foil of a metal such as aluminum that is stable in the potential range of the positive electrode 11, a film with the metal disposed on the surface, or the like can be used. The thickness of the positive electrode core is, for example, 10 μm to 30 μm. The positive electrode mixture layer contains a positive electrode active material, a binder, and a conductive material, and is preferably provided on both sides of the positive electrode core except for the part to which the positive electrode lead 19 is connected. The positive electrode 11 can be produced, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a binder, a conductive material, and the like to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode mixture layer on both sides of the positive electrode core.
[0023] The positive electrode active material contains lithium transition metal oxide as a main component. The positive electrode active material may be substantially composed of only lithium transition metal oxide, or may be a material in which inorganic compound particles such as aluminum oxide and lanthanoid-containing compounds are fixed to the surface of lithium transition metal oxide particles. The lithium transition metal oxide may be used alone or in combination of two or more kinds.
[0024] Examples of metal elements contained in the lithium transition metal oxide include nickel (Ni), cobalt (Co), manganese (Mn), aluminum (Al), boron (B), magnesium (Mg), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), gallium (Ga), strontium (Sr), zirconium (Zr), niobium (Nb), indium (In), tin (Sn), tantalum (Ta), and tungsten (W). An example of a suitable lithium transition metal oxide is represented by the general formula: Li α Ni x M (1―x) O 2(0.1≦α≦1.2, 0.3≦x<1, M contains at least one of Co, Mn, and Al). For example, NCA, in which part of the nickel is replaced with cobalt and aluminum is added, is used as the positive electrode material.
[0025] Examples of the conductive material contained in the positive electrode mixture layer include carbon materials such as carbon black, acetylene black, ketjen black, carbon nanotubes, carbon nanofibers, and graphite. Examples of the binder contained in the positive electrode mixture layer include fluororesins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyimide resins, acrylic resins, and polyolefin resins. These resins may be used in combination with cellulose derivatives such as carboxymethylcellulose (CMC) or its salt, and polyethylene oxide (PEO).
[0026] [Negative electrode] The negative electrode 12 has a negative electrode core and a negative electrode mixture layer provided on the surface of the negative electrode core. For the negative electrode core, a foil of a metal such as copper that is stable in the potential range of the negative electrode 12, a film with the metal disposed on the surface, or the like can be used. The thickness of the negative electrode core is, for example, 5 μm to 15 μm. The negative electrode mixture layer contains a negative electrode active material and a binder, and is preferably provided on both sides of the negative electrode core except for the part to which the negative electrode lead 20 is connected. The negative electrode 12 can be produced, for example, by applying a negative electrode mixture slurry containing a negative electrode active material and a binder, etc., to the surface of the negative electrode core, drying the coating, and then compressing it to form a negative electrode mixture layer on both sides of the negative electrode core. A conductive material may be added to the negative electrode mixture slurry. The conductive material can make the conductive path uniform. The negative electrode mixture layer may also contain a conductive material such as acetylene black, similar to the positive electrode mixture layer.
[0027] The negative electrode mixture layer contains, as a negative electrode active material, a compound represented by the general formula M 3 Me 2 X 7(wherein M contains at least one of La and Ca, Me contains at least one of Mn, Ni, Fe and Co, and X contains at least one of Ge, Si, Sn and Al) 3 Me 2 X 7 A specific example of a suitable negative electrode active material is La 3 Co 2 Sn 7 , La 3 Mn 2 Sn 7 , La 3 Ni 2 Sn 7 Among them, from the viewpoint of increasing capacity, La 3 Co 2 Sn 7 Or La 3 Ni 2 Sn 7 is preferred, and La 3 Ni 2 Sn 7 is particularly preferred.
[0028] The negative electrode active material M 3 Me 2 X 7 The particle size of M is preferably 1 to 30 μm, more preferably 2 to 20 μm, and particularly preferably 2 to 10 μm. 3 Me 2 X 7 If the particle size of M becomes too large, the reactivity with Li decreases, and the contact area between the particles decreases, increasing the resistance. On the other hand, if the particle size becomes too small, the packing density of the negative electrode active material decreases, and it is expected that the capacity will decrease. 3 Me 2 X 7 The average particle size of the powder is, for example, 3 to 15 μm, or 5 to 10 μm. 3 Me 2 X 7 The particle size of the negative electrode mixture layer is measured by scanning electron microscope (SEM) in a cross-sectional image. 3 Me 2 X 7 It is measured as the diameter of the circumscribed circle of a particle. The average particle size is calculated by averaging the particle sizes of 100 random particles.
[0029] M 3 Me 2 X 7 The intermetallic compound represented by the formula (I) can be formed by arc melting, and it is preferable to anneal after arc melting. Regarding M, La may be substituted up to about 50%. For example, when about 40% of La was substituted with Ca, a large charge / discharge capacity (initial charge capacity 301 mAh / g, initial discharge capacity 223 mAh / g (1718 mAh / cc)) and a small volume change rate (0.5% or less) were obtained.
[0030] The negative electrode active material is M 3 Me 2 X 7 Contains as the main component (the component with the highest mass ratio), and essentially M 3 Me 2 X 7 On the other hand, the negative electrode active material may be composed of only M 3 Me 2 X 7 Other active materials, such as intermetallic compounds other than those mentioned above, carbon-based active materials such as graphite, or Si-based active materials containing Si, may be used in combination. For example, when graphite is used in combination, the content of graphite may be 50 to 90% by mass with respect to the mass of the negative electrode active material.
[0031] The binder contained in the negative electrode mixture layer is water-based ammonium carboxymethyl cellulose (NH 4 -CMC) is used. It is also preferable to further include styrene butadiene rubber (SBR). Water-based binders such as water-based urethane and water-based acrylic polymers can also be used.
[0032] The mass ratio of the binder to the negative electrode active material is preferably 0.3 wt % or more and 5.0 wt % or less. 4 The ratio of CMC to SBR is preferably about 2:0.5 to 2.
[0033] [Separator] A porous sheet having ion permeability and insulating properties is used for the separator 13. Specific examples of the porous sheet include a microporous membrane, a woven fabric, and a nonwoven fabric. The material of the separator 13 is preferably an olefin resin such as polyethylene or polypropylene, or cellulose. The separator 13 may have either a single-layer structure or a laminated structure. A heat-resistant layer containing a heat-resistant material may be formed on the surface of the separator 13. Examples of the heat-resistant material include polyamide resins such as aliphatic polyamides and aromatic polyamides (aramids), and polyimide resins such as polyamideimides and polyimides.
[0034] <Example> The present disclosure will be further described below with reference to examples, but the present disclosure is not limited to these examples.
[0035] [Preparation of negative electrode] As the negative electrode active material, La with a particle diameter of 2 to 20 μm 3 Ni 2 Sn 7 The binder was SBR / CMC, and the conductive material was artificial graphite SP5030. 3 Ni 2 Sn 7 / NH 4 -CMC / SBR / SP5030 were mixed in a mass ratio of 85.5 / 3 / 1.5 / 10 to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry was applied onto a negative electrode core made of copper foil, and the coating was dried and compressed, and then cut into a predetermined electrode size to obtain a negative electrode. Note that the copper foil may be one with a roughened surface and a thickness of about 18 μm.
[0036] [Preparation of test cell] The negative electrode and a positive electrode made of lithium metal foil were arranged opposite each other with a separator interposed therebetween to form an electrode assembly, which was then housed in an outer can. A predetermined non-aqueous electrolyte solution was poured into the outer can, and the outer can was then sealed to obtain a two-electrode cell (non-aqueous electrolyte secondary battery).
[0037] Here, the electrolyte is 1.0M LiPF 6The EC / EMC solvent was prepared by adding
[0038] [Charge / discharge test (capacity evaluation)] The obtained test cell was charged at a constant current (CC) of 0.2 C at room temperature to a battery voltage of 0.01 V (the potential of the negative electrode relative to metallic lithium was 0.01 V) and 1.5 V (the potential of the negative electrode relative to metallic lithium was 1.5 V) to examine the change in the electrode voltage. In addition, the cell was repeatedly discharged at a constant current and then charged at a constant current, and the charge capacity and discharge capacity were measured for each cycle.
[0039] [result] Figure 2 shows a binder, styrene butadiene rubber / ammonium carboxymethyl cellulose (SBR / NH 4 The X-ray diffraction patterns of the electrodes are shown for an example using SBR / NH 4 It can be seen that in the examples using -CMC, no impurity alloy phase is formed.
[0040] 3A and 3B are graphs showing the charge / discharge characteristics in the example. FIG. 3A is a graph showing the relationship between capacity and electrode potential, and FIG. 3B is a graph showing the relationship between cycle number and capacity.
[0041] In this way, SBR / NH 4 In the example using -CMC, it can be seen that there is almost no deterioration even after three charge / discharge cycles. In addition, even after 29 charge / discharge cycles, the change in the charge / discharge curve is small, and 99.5% of the initial charge / discharge capacity is maintained, demonstrating good cycle characteristics.
[0042] Fig. 4 shows the charge-discharge characteristics of Comparative Example 1, which uses SBR / Na-CMC as the negative electrode binder. As described above, it was found that Comparative Example 1 had poor cycle characteristics, with the capacity decreasing with repeated charge-discharge. This is believed to be due to the alloying reaction shown in Fig. 2.
[0043] Table 1 shows the La 3 Ni 2 Sn 7 ,La 1.8 Ca 1.2 Ni 2 Sn 7 1 is a table showing an evaluation of binders for various negative electrode active materials.
[0044] [Table 1]
[0045] In this way, the negative electrode mixture layer is La 3 Ni 2 Sn 7 ,La 1.8 Ca 1.2 Ni 2 Sn 7 The results were the same regardless of whether PVdF was used or not. In other words, PVdF is prone to gelation during application, so it is necessary to use it with care (△ 1 ) Gelation during coating can be suppressed by adding maleic anhydride. PAN requires the use of organic solvents, which increases the manufacturing cost (△ 2 In addition, alloys are generated during coating in PI and SBR / Na-CMC, which reduces cycle characteristics (△ 3 ) and the example, SBR / NH 4 -CMC is water-based and does not require organic solvents, does not produce alloys, has good cycle characteristics, and is suitable as a binder (good).
[0046] The negative electrode mixture layer is represented by the general formula M 3 Me 2 X 7(wherein M includes at least one selected from the group consisting of La, Sr, Ca, Mg, and Y, Me includes at least one selected from the group consisting of Mn, Ni, Fe, Co, and Cu, and X includes at least one selected from the group consisting of Ge, Si, Sn, Al, and B), 4 -CMC) has been found to be suitable.
[0047] Thus, the general formula M 3 Me 2 X 7 (wherein M includes at least one selected from the group consisting of La, Ce, Ba, Sr, Zr, Ca, Mg, and Y, Me includes at least one selected from the group consisting of Ti, V, Cr, Nb, Mn, Ni, Fe, Co, and Cu, and X includes at least one selected from the group consisting of Ge, Si, Sn, Al, P, Sb, and B), 4 -CMC) is suitable as a binder. [Explanation of symbols]
[0048] 10 Secondary battery 11 Positive electrode 12 Negative electrode 13 Separator 14 Electrode body 15 Exterior body 16 Sealing body 17,18 Insulating plate 19 Positive lead 20 Negative lead 21 Grooved part 22 Filters 23 Lower valve body 24 Insulating materials 25 Upper valve 26 Cap 26a opening 27 Gasket
Claims
1. A lithium ion battery comprising: a positive electrode having a positive electrode mixture layer containing a positive electrode active material; and a negative electrode having a negative electrode mixture layer containing a negative electrode active material, the lithium ions moving between the positive electrode and the negative electrode to perform charging and discharging, The negative electrode mixture layer is General formula M 3 Me 2 X 7 (wherein M includes at least one selected from the group consisting of La, Ce, Ba, Sr, Zr, Ca, Mg, and Y, Me includes at least one selected from the group consisting of Ti, V, Cr, Nb, Mn, Ni, Fe, Co, and Cu, and X includes at least one selected from the group consisting of Ge, Si, Sn, Al, P, Sb, and B), and Ammonium carboxymethylcellulose (NH 4 -CMC) and a binder; Including, lithium ion batteries.
2. A lithium ion battery comprising: a positive electrode having a positive electrode mixture layer containing a positive electrode active material; and a negative electrode having a negative electrode mixture layer containing a negative electrode active material, the lithium ions moving between the positive electrode and the negative electrode to perform charging and discharging, The negative electrode mixture layer is General formula M 3 Me 2 X 7 (wherein M includes at least one selected from the group consisting of La, Sr, Ca, Mg, and Y, Me includes at least one selected from the group consisting of Mn, Ni, Fe, Co, and Cu, and X includes at least one selected from the group consisting of Ge, Si, Sn, Al, and B), Ammonium carboxymethylcellulose (NH 4 -CMC) and a binder; Including, lithium ion batteries.
3. The binder further includes another aqueous binder.
3. The lithium ion battery according to claim 1 or 2.
4. The other aqueous binder is styrene butadiene rubber (SBR). The lithium ion battery of claim 3.
5. The lithium ion battery according to any one of claims 1 to 4, wherein a mass ratio of the binder to the negative electrode active material is 0.3 wt % or more and 5.0 wt % or less.
Citation Information
Patent Citations
Non-aqueous electrolyte secondary battery
JP2005100773A
Nonaqueous electrolyte secondary battery
JP2005310739A
Nonaqueous electrolyte battery
JP2007073215A
Negative electrode and battery
JP2007258127A
Negative electrode for nonaqueous electrolyte secondary battery and the nonaqueous electrolyte secondary battery
JP2010218855A
